2021
DOI: 10.1515/jbcpp-2021-0159
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and management of asymptomatic SARS-CoV-2 infections

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has caused and is still causing tremendous morbidity, mortality, and damage to our societies. The disease course of COVID-19 can be unpredictable ranging from asymptomatic infections to multi-organ failure and death. Transmission of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) from an asymptomatic infected individual to others has been observed early in the pandemic. Asymptomatic individuals have been shown to have quantitative SARS-CoV-2 viral l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…After infection with SARS-CoV-2, an immune response occurs in the human body to produce immunoglobulins corresponding to the antigen. Studies have shown that SARS-CoV-2 is highly infectious ( Harrison et al, 2020 ), and the production of variants ( Harvey et al, 2021 ; Tao et al, 2021 ) and the increase in asymptomatic infections ( Johansson et al, 2021 ; Tanriover et al, 2021 ) have growth its transmission rate. Infection with SARS-CoV-2 affects multiple organs, as ACE2 is present in large numbers in human lung and small intestine epithelial cells, making the respiratory ( Mandal et al, 2021 ; Stavem et al, 2021 ) and digestive ( Aiyegbusi et al, 2021 ) systems susceptible to viral attack and disease, and it has also been documented that ACE2 is also expressed in the bile ducts, thus predisposing to liver injury ( Hamming et al, 2004 ; Yang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…After infection with SARS-CoV-2, an immune response occurs in the human body to produce immunoglobulins corresponding to the antigen. Studies have shown that SARS-CoV-2 is highly infectious ( Harrison et al, 2020 ), and the production of variants ( Harvey et al, 2021 ; Tao et al, 2021 ) and the increase in asymptomatic infections ( Johansson et al, 2021 ; Tanriover et al, 2021 ) have growth its transmission rate. Infection with SARS-CoV-2 affects multiple organs, as ACE2 is present in large numbers in human lung and small intestine epithelial cells, making the respiratory ( Mandal et al, 2021 ; Stavem et al, 2021 ) and digestive ( Aiyegbusi et al, 2021 ) systems susceptible to viral attack and disease, and it has also been documented that ACE2 is also expressed in the bile ducts, thus predisposing to liver injury ( Hamming et al, 2004 ; Yang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Vaccination has been crucial in preventing asymptomatic infections. Real-life data continue to demonstrate the effects of community vaccination in breaking the transmission chain of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) 2 . The Indonesian Food and Drug Supervisory Agency has issued an Emergency Use Authorization (EUA) for five commercial COVID-19 vaccine products, including CoronaVac produced by Bio Farma, Pfizer, AstraZeneca, Moderna, and Zifivax 3 .…”
Section: Introductionmentioning
confidence: 99%
“…LFTs' limited ability to reliably detect infection in asymptomatic carriers or most pre-symptomatic infections is their greatest weakness. Thus, their widespread use as a population-based test to prevent contact spread is questionable [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%